Optimization of extraction conditions for antioxidant activity of crude bioactive phenolics from Phanerochaete Chyrsosporium - Kuppusamy, Pravinnaat (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
Phanerochaete chrysosporium known as white rot fungus has the ability to degrade the abundant aromatic polymer lignin. In this study, the extractions for antioxidant activity of Phanerochaete chrysosporium biomass extract were determined by using Central Composite Experimental Design. The extraction conditions studied were solid-to-solvent ratio, extraction pH and extraction time, while agitation speed, temperature and solvent concentration was set at the minimum value. All three parameters used give significant value which are then can be proceed for the optimization process. Folin-Ciocalteu reagents were used to determined the total phenolic content while 2,2-diphenyl-1-picryhydrazyl (DPPH) scavenging assay was used to analyze the antioxidant activity. From the result, there were no correlation found between total phenolic compounds and antioxidant activity.